Culinary Potential of Traditional Lotek as Culinary Tourism Attraction in Karawang Regency (case study: Lotek Ci Apang) - Susanto, Prayogo; Dewantara, Yudhiet Fajar; Chandra, Carine; Handoko, Syheravi (Gema Wiralodra, 2025)
Lotek Ci Apang is a restaurant with lotek as its main menu. Lotek itself is a traditional culinary dish originating from West Java, making it a familiar food in the West Java region. This study aims to explore the potential of lotek as a culinary tourism attraction in Karawang Regency, which will become one of the culinary tourism attractions in Karawang Regency. Therefore, the researcher wants to know more about the potential of culinary tourism attractions at Lotek Ci Apang. The purpose of this study is to determine the potential of culinary tourism attractions by using the 4A analysis method. This type of research uses a qualitative method with data collection through observation, interviews, and documentation. The analysis uses the theory of tourist attractions to determine the potential of traditional cuisine. This paper aims to analyze Lotek Ci Apang restaurant to determine the potential of traditional cuisine as a tourist attraction from the restaurant owner, which will later develop culinary tourism in Karawang Regency through lotek dishes.